PAD4 Immunization Triggers Anti-Citrullinated Peptide Antibodies in Normal Mice: Analysis With Peptide Arrays - Hemon, Marie F.; Lambert, Nathalie C.; Arnoux, Fanny; Roudier, Jean; Auger, Isabelle (Frontiers in Immunology, 2022)
The critical immunological event in rheumatoid arthritis (RA) is the production of antibodies to citrullinated proteins (ACPAs), ie proteins on which arginines have been transformed into citrullines by peptidyl arginine deiminases (PAD). In C3H mice, immunization with PAD4 triggers the production of ACPAs. Here, we developed a peptide array to analyze the fine specificity of anti-citrullinated peptide antibodies and used it to characterize the ACPA response after hPAD4 immunization in mice expressing different H-2 haplotypes. Sera from C3H, DBA/2, BALB/c and C57BL/6 mice immunized with human PAD4 (hPAD4) or control-matched mice immunized with phosphate buffered saline (PBS) were used to screen peptide arrays containing 169 peptides from collagen, filaggrin, EBNA, proteoglycan, enolase, alpha and beta fibrinogen, histon and vimentin. Human PAD4 immunization induced antibodies directed against numerous citrullinated peptides from fibrinogen, histon 4 and vimentin. Most peptides were recognized under their arginine and citrullinated forms. DBA/2 and BALB/c mice (H-2d) had the lowest anti-citrullinated peptide IgG responses. C3H (H-2k) and BL6 mice (H-2b) had the highest anti-citrullinated peptide IgG responses. The newly developed peptide array allows us to characterize the ACPA production after hPAD4 immunization in mice on the H-2d, H-2k or H-2b backgrounds. This sensitive tool will be useful for further studies on mice for prevention of ACPA production by PAD tolerization.